The Peruvian State no one writes - Mendívil Nina, José (2021)
On the much-needed reform of the State little to almost nothing it has been done, as we pretend to show in this academic article. In this essay emphasis is not only to highlight the unnecessary and persistent polarization that continues reducing the possibilities and prospects of any step taken towards political reform and administrative modernization of the State: They are the orphanages in which are both theory political and constitutional they found locked in trivial matters and so continue until not authentically initiate a public debate on the future of the Peruvian republic, and also that this thematic approach is not reduced to the elites of intellectuals and politicians. Urge have a modern and efficient state, and thus, at least, trying to overcome the problems of regionalization and decentralization of power and the administration of the public good'; particularly to overcome the constraints of 'extractive model having a common perspective on our present, which should not be reduced to the government of the day, but be extended to at least also for the next three governments, political perception of what should will be present from requiring our governance to start building the future of the nation in a different world than we know so far, which will profoundly change between the late XXI and early twenty-second century, world probably I suspect, will be a world in which the masses will not have much importance in the evolution of society and the elites of our political class will not have modern slaves' to which represent elites who perhaps more accurate is call political subclass 'because daily show in the Congress and other forums are how far imagine the future that the country should start building.The main course of my ideas about politics and the future of our nation that I raise in a frank and conversational tone is to this policy that was decisive until the end of the twentieth century to the disputes of interests and the conquest of power by different means, something that has been said and that we must avoid repetition of sterility involved in the future where technology, science and governance will give the world a new configuration.